The evaluation of the effect of fracture geometry on permeability based on laboratory study and numerical modelling (Rudarsko-geološko-naftni zbornik, 2021)
The geometry of fractures includes orientation, spacing, aperture are among the parameters affecting permeability in rocks. Studying the effect of fractures geometry on the permeability in a laboratory scale requires the selection of a suitable sample in terms of physical and mechanical properties. Therefore, in this study, fibrous fiber was selected due to low water absorption and permeability as well as its non-brittle behavior and flexibility. In order to investigate the effect of fracture geometry on the permeability, 1, 2, 3, and 4 fractures with spacing greater than 50 mm, 50 mm, 25 mm, and 15 mm and with orientations of 0, 15, 30, 45, and 60 degrees to the horizon in the sample were created. The fractures did not come into contact with the surface of the sample .The results showed that the permeability raises exponentially with increasing orientation and decreasing the spacing. This situation is mostly seen in fractures with orientations larger than 30 degrees. Also, the permeability measured in the laboratory was compared with the results obtained from the numerical method of distinct elements and UDEC software. The results showed an error of about 10-15%, which is well-matched between the permeability obtained from the laboratory and the numerical method.